(untitled) (International Journal of Language, Literacy and Translation, 2025)
This study examines the influence of the modality on translator style through a multidimensional analysis of five English translations of Ah Q Zhengzhuan. Employing a mixed-method approach, the research integrates quantitative analysis using Multidimensional Analysis (MDA) framework (Biber, 1988) and Multidimensional Analysis Tagger (MAT) proposed by Nini (2019) to investigate the use of necessity, possibility, and predictive modals across the translations. Complementing the quantitative data, a qualitative analysis explores specific examples of modal choices made by each translator, providing deeper insights into their stylistic and cultural strategies. The findings indicate that Leung and Lyell favour stronger predictive modals, thereby reinforcing future certainty and maintaining the authoritative tone of the original text, while Lovell and Wang tend to balance the use of possibility and necessity modals, resulting in a more adaptive narrative style. This study offers practical implications for translators by illustrating how modality influences the expression of authority, certainty and cultural reproduction in translation, contributing to a broader understanding of the translator’s style. By bridging quantitative and qualitative methodologies, the research provides original insights into the modality’s role in cross-cultural literary translations and its impact on both narrative tone and cultural interpretation.